MAKNA UGATAMEE SEBAGAI “YANG IMANEN” DALAM KEPERCAYAAN TRADISIONAL SUKU MEE PANIAI-PAPUA - Aris Yeimo; Donatus Sermada Kelen (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
The focus of this article is on the concept of God (Ugatamee) in the traditional faith of the Mee tribe in Paniai - Papua in and through the prayer traditions that have been passed down from generation to generation by their ancestors. They believe that Ugatamee is always present "here and now". Ugatamee is not a person who lives apart from all the struggles of their lives. Expressions of gratitude for Ugatamee's involvement in their lives are expressed through ritual forms of prayer. The methodology used in working on this article is descriptive-qualitative by analyzing scientific journals and books as well as interviews. This article contributes to the understanding of Ugatamee identity and the meaning of Ugatamee's communicative and participatory presence "here and now".